Pengaruh Bauran Pemasaran Jasa Terhadap Nilai dan Niat Berperilaku Pelanggan Hotel Syariah Grand Kalimas di Surabaya - Fatimah, Nur Hadziqotul (Jurnal Ekonomi dan Bisnis Islam, 2015)
This research aims to determining the influence of service marketing mix on customer value and behavioral intention of Grand Kalimas Sharia Hotel Surabaya.This research is a quantitative research by using path analysis test. The population characteristic of this research is the customers who are now staying or having been staying during January 2015. The samples of this research are 30 respondents. The sampling technic is simple random sampling. Result shows that service marketing mix is significantly influencing on customers value, customers value significantly influencing customers behavioral intentions, meanwhile service marketing mix is not giving a significant influence on behavioral intentions. The chairman of Grand Kalimas Sharia Hotel Surabaya is suggested to improve the hotel facilities, broadening the parking lot, and intensively giving a special promo for attracting new customers. Also, the hotel can innovate by creating a member card to create a bond with the customers.Â Keywords: Servicemix, customers value, customers behavioral intention